Pengaruh Kinerja Keuangan dan Karakteristik Perusahaan terhadap Kuantitas dan Kualitas Pengungkapan Sustainability Report di Indonesia Periode 2013-2015 - Lyndia Yoslin Damanik (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2017)
The purpose of this research is to examine the influence of financial performance and company characteristics consist of the company type and company size against the quantity and quality of disclosure Sustainability Report. Sample in this research is determined by using purposive sampling that selected according to certain criteria. The criteria used were as follows: (1) Indonesian companies that publish Sustainability Reports to GRI through the comprehensive www.globalreporitng.org website from 2013 to 2015. (2) Publish the complete Annual Report from 2013 to 2015. (3) The disclosure standard uses GRI-G4, if the format is not in GRI-G4 then conversion were made. Data collection techniques were conducted using secondary data by conducting document review of Sustainability Report and Annual Report. Companies that become the sample of this research there were 29 Companies. The reporting periods start from 2013 to 2015 or as many as 3 years. Dependent variables that have been studied were the quantity and quality of disclosure Sustainability Report called Index of Disclosure Quantity (IPN) and Index of Disclosure Quality (IPL) of Sustainability Report. Disclosure obtained by using content analysis method based on measurement proposed by Gunawan, et al (2009). The Independent variable that have been studied here were Financial Performance measured using Return on Assets (ROA) and Company Characteristics consisting of Company Type (TYPE) and Company Size (LGTASZ).The result of the research showed that the Company's Financial Performance influenced the Quantity and Quality of Sustainability Report Disclosure. The size of the company did not affect the quantity and the quality of Sustainability Report Disclosure. Corporate Type influenced the Quantity of Sustainability Report Disclosure, while the Company Type did not affect the Quality of Sustainability Report Disclosure.